Beispiel Nr: 19
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +1 y =2\\ 3 x +3 y = 3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 1 x +1 y =2\\ II \qquad 3 x +3 y = 3 \\ \text{I nach y auflösen}\\ 1 x +1 y =2 \\ 1 x +1 y =2 \qquad /-1 x\\ 1 y =2 -1 x \qquad /:1 \\ y =2 -1 x \\ \text{II nach y auflösen}\\ 3 x +3 y =3 \\ 3 x +3 y =3 \qquad /-3 x\\ 3 y =3 -3 x \qquad /:3 \\ y =1 -1 x \\ \text{I = II}\\ 2 -1 x =1 -1 x \qquad /+1 x /-1 \\ 2-1 =-1 x +1 x \\ \\ L=\{\}\end{array} & \begin{array}{l} I \qquad 1 x +1 y =2\\ II \qquad 3 x +3 y = 3 \\ \text{I nach x auflösen}\\ 1 x +1 y =2 \\ 1 x +1 y =2 \qquad /-1 y\\ 1 x =2 -1 y \qquad /:1 \\ x =2 -1 y \\ \text{II nach x auflösen}\\ 3 x +3 y =3 \\ 3 x +3 y =3 \qquad /-3 y\\ 3 x =3 -3 y \qquad /:3 \\ x =1 -1 y \\ \text{I = II}\\ 2 -1 y =1 -1 y \qquad /+1 y /-1 \\ 2-1 =-1 y +1 y \\ \\ L=\{\}\end{array} \end{array} $